2001
DOI: 10.1177/0272431601021002003
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Parent/Adolescent Attachment and Aggression in Young Adolescents

Abstract: A model of the association between adolescents’ perception of the quality of parent/adolescent attachment and adolescent aggression was examined, with social cognition and self-esteem as mediators. A total of 68 sixth graders, their parents, and their language arts teachers participated. Adolescents completed measures of attachment with mother and with father, self-esteem, social cognition, and aggressive tendencies. Mothers, fathers, and teachers each completed measures of adolescent aggressive and prosocial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 37 publications
9
71
2
Order By: Relevance
“…Recent research has indicated that attachment relationships with mothers and fathers are differentially related to outcomes. For example, Simons, Paternite, and Shore (2001) found that attachment to mothers but not with fathers was predictive of adolescent self-esteem, views of others, and aggression. Marcus and Betzer (1996) also found attachment to fathers to be the strongest predictor of antisocial behavior.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Recent research has indicated that attachment relationships with mothers and fathers are differentially related to outcomes. For example, Simons, Paternite, and Shore (2001) found that attachment to mothers but not with fathers was predictive of adolescent self-esteem, views of others, and aggression. Marcus and Betzer (1996) also found attachment to fathers to be the strongest predictor of antisocial behavior.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…These confounding family environment factors may account for many of the links with psychopathology that are seen in studies of harsh discipline, and raise the possibility that it is not necessarily harsh discipline per se that is harmful. This study examined three other measures of parenting, warmth, quality of attachment, and firm control, that are known to relate to adolescent outcomes (Jones, Forehand, & Beach, 2000;Matza, Kupersmidt, & Glenn, 2001;Simons, Paternite, & Shore, 2001), and thus may act as alternative explanations of the effects of harsh discipline. Another limitation of the research on parental discipline has been its consideration of physical abuse as a dichotomous variable (e.g., Williamson, Borduin, & Howe, 1991).…”
mentioning
confidence: 99%
“…Kerns et al (1996) noted that securely attached fifth-graders were more accepted by their peers, whereas Granot and Mayseless (2001) found that insecurely attached fourth-and fifth-graders were more rejected by peers. , Finnegan, Hodges, and Perry (1996) found that third-grade to seventh-grade boys who reported greater use of preoccupied (i.e., insecure-ambivalent) coping strategies with their attachment figure when faced with everyday stressors requiring emotion regulation were more likely nominated by their peers as immature and victimized and used a hovering peer entry style.Attachment and psychosocial adjustment-Children who feel secure and supported by their primary caregivers have been shown to have higher levels of perceived competence in multiple domains (Kerns et al, 1996), have higher self-esteem (Simons, Paternite, & Shore, 2001) and feel less lonely (Kerns et al, 1996). Furthermore, relatively lower security has been associated with both internalizing and externalizing problems (Granot & Mayseless, 2001; McCartney, Owen, Booth, Clarke-Stewart, & Vandell, 2003).…”
mentioning
confidence: 99%